A tendência vinculante das súmulas e orientações jurisprudenciais trabalhistas no sistema civil law - Almeida, Caroline Zangerolami Garcia Paes de (2016)
The purpose of this work is to study the binding trend of the labor precedents and case law directives, taking into consideration the position currently adopted by the Courts who make mandatory use of these institutions. In order to so, an analysis of the common law and civil law legal systems had to be made, by performing a historic research and presenting its conceptual, structural and rule applicability divergences, as well as the favorable and unfavorable arguments related to the validity of the application of these items in our country. Before expressing any opinion regarding the applicability between the systems, it was necessary to think critically and to reflect on the sociological reality of Brazil and the manner in which the judiciary branch is currently conducted. We have verified that the precedents issued by the Superior Labor Court are inevitably endowed with a binding trend and, thus, must go through the means of control and validity of our system